Maternal Hypertension as a Dominant Predictor of Neonatal Respiratory Distress Syndrome: A Cross-Sectional Study in a Regional Indonesian Hospital (Open Access Indonesian Journal of Medical Reviews, 2025)
Neonatal respiratory distress syndrome (RDS) remains a significant cause of morbidity and mortality in newborns, particularly in developing countries. While prematurity is a primary risk factor, other maternal and neonatal factors, including maternal hypertension, contribute to its incidence. This study aimed to identify the risk factors for RDS in neonates treated at a regional hospital in Tabanan, Indonesia, with a particular focus on the role of maternal hypertension. A cross-sectional study was conducted using secondary data from medical records of neonates treated at Tabanan Regional General Hospital (RSUD) from January 2023 to December 2024. The study included neonates diagnosed with RDS and a control group without RDS. Data on maternal factors (hypertension, diabetes mellitus) and neonatal factors (gestational age, birth weight, gender, mode of delivery) were collected. Bivariate analysis using Chi-square and Fisher's exact tests was performed to determine associations, with a p-value
Keywords: Cross-sectional study; Maternal hypertension; Neonatal respiratory distress syndrome; Neonates; Risk factors